Perubahan Kepadatan Bangunan PermukimanTerdampak Perkembangan Aglomerasi Industri di Kecamatan Gondangrejo, Kabupaten Karanganyar - Sirotulmustaqim, Dikri; Andini, Isti; Widodo, Candraningratri Ekaputri (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The 2013-2031 Karanganyar Regency RTRW directs Gondangrejo District as an area designated for medium to large-scale industries, although on the other hand there are rural settlement areas in existing conditions. The industry in Gondangrejo District is growing and developing which is agglomerated along the Solo-Purwodadi Road. The development of this agglomeration has an impact on the increasing density of rural settlements around the industry. Therefore, this study aims to measure changes in the density of residential buildings affected by the development of industrial agglomeration in Gondangrejo District, Karanganyar Regency between 2004-2024. The research method used is quantitative with regional relative comparison analysis techniques, average nearset neighbors, and kernel density analysis. The results of the study show that industrial agglomeration in Gondangrejo District has experienced low-level development. The density of residential buildings has also increased to 25 units/ha. The growth of residential buildings, boarding houses, shops/stalls, and parking facilities around the industry is a direct impact of the development of industrial agglomeration on the density of residential buildings.